2020
DOI: 10.3390/v12020241
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HIV-1 Envelope Mutations that Enhance Entry Using Macaque CD4 and CCR5

Abstract: Although Rhesus macaques are an important animal model for HIV-1 vaccine development research, most transmitted HIV-1 strains replicate poorly in macaque cells. A major genetic determinant of this species-specific restriction is a non-synonymous mutation in macaque CD4 that results in reduced HIV-1 Envelope (Env)-mediated viral entry compared to human CD4. Recent research efforts employing either laboratory evolution or structure-guided design strategies have uncovered several mutations in Env's gp120 subunit … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…We benchmark our models on a series of viral protein deep mutational scans [1][2][3][4][5][6][7][8][9][10][11][12][13][51][52][53][54][55][56][57][58] (Table S2, Table S4). For each viral mutational scan, we select the variable or variables of protein fitness or antibody escape treated as primary in the publications.…”
Section: Deep Mutational Scansmentioning
confidence: 99%
“…We benchmark our models on a series of viral protein deep mutational scans [1][2][3][4][5][6][7][8][9][10][11][12][13][51][52][53][54][55][56][57][58] (Table S2, Table S4). For each viral mutational scan, we select the variable or variables of protein fitness or antibody escape treated as primary in the publications.…”
Section: Deep Mutational Scansmentioning
confidence: 99%
“…In addition, studies on the effect of host genes on susceptibility to HIV infection and the rate of disease progression have shown that host genes are associated with a signi cant number of individual genes. Other words, the susceptibility of population may attribute to the polymorphism of key genes, such as proteins related to control viral entry (CCR5, CCR2, RANTES, and SDF1) [45][46][47][48], immune regulation (IL-10, TNF-α, and MBL-2) [49,50] and adaptive immune recognition by T-cells (human leukocyte antigen or HLA) [51].…”
Section: Discussionmentioning
confidence: 99%
“… a) EVE predictions are well correlated with a broad range of viral surface protein deep mutation scanning experiments surveying protein replication and function for SARS-CoV-2 RBD 30 , 31 and M pro32 , H1N1 hemagglutinin 26 , 27 and HIV env 25 , 28 , 29 . b) Site-averaged EVE predictions have similar correlations with site-averaged SARS-CoV-2 RBD DMS experiments as Potts model DCA 37 or EVmutation 21 .…”
Section: Extended Data Figures and Tablesmentioning
confidence: 94%
“…Consequently, EVE considers dependencies across positions (epistasis), capturing the changing effects of mutations as the dominant strain backgrounds diversify from the initial sequence [23][24][25] . We demonstrate the efficacy of EVE by comparing model predictions and data from mutational scanning experiments that measure several facets of fitness for thousands of mutations to viral proteins [25][26][27][28][29][30][31][32] . Model performance approaches the Spearman correlation (ρ) between experimental replicates, including viral replication for influenza 26 (ρ = 0.53) and HIV 25 (ρ = 0.48) (Extended Data Fig.…”
Section: Evescape Combines Deep Learning Models and Biophysical Const...mentioning
confidence: 99%